Efficiency of Ultrasonic Incorporated Glutathione Treatment in Preserving the Physicochemical Quality and Preventing the Browning of Lotus Rhizome Slices. (13th September 2021) - Wen, Bo; Li, Da; Du, Xianfeng; Kedbanglai, Phacharee; Tang, De; Huang, Zhen; Ge, Zibing; Supapvanich, Suriyan
Abstract: This study investigated the efficacy of 40‐kHz (200 W) ultrasonication (US) for 2 min combined with glutathione (GSH) at 0.5% w/v (US + GSH) in preventing browning and preserving the physicochemical quality of lotus rhizome slices stored in a 4 ± 1 °C refrigerator. According to the visual appearance of the slices, US + GSH treatment more effectively inhibited the browning of the cut surface than did GSH or US treatment alone. US + GSH and GSH treatments were more effective than US and control treatments in preserving the slices' colour attributes, such as their lightness and whiteness index values, and potentially retarded enzymatic browning reactions and increases in browning index and total colour difference values. Moreover, the application of US and US + GSH treatments noticeably preserved the texture of the slices. None of the treatments affected the total sugar content during storage. The US + GSH treatment markedly enhanced the ferric reducing antioxidant potential of the slices during storage. The slices treated with US, GSH, and US + GSH exhibited slower reductions in 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) free radical scavenging activity than did the controls. In conclusion, US + GSH treatment is a feasible approach for inhibiting browning, maintaining texture, and inducing antioxidant activity in lotus rhizome slices during storage. Abstract : Ultrasonic incorporated with glutathione preventing browning, maintaining texture, and enhancing bioactive compounds of lotus root slices.